2021
DOI: 10.3390/ijerph18115544
|View full text |Cite
|
Sign up to set email alerts
|

The Organizational Atmosphere in Israeli Hospital during COVID-19: Concerns, Perceptions, and Burnout

Abstract: The COVID-19 crisis poses challenges to healthcare systems and requires micro- and macro-organizational adaptations. This study examined the organizational atmosphere in Israeli hospitals by evaluating workers’ perceptions and concerns about the COVID-19 crisis and its management. At the end of the pandemic’s first wave in Israel, 547 healthcare workers responded to an online survey, which inquired about COVID-19 concerns at the individual and family level, perceptions at the national and organizational level,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
(33 reference statements)
1
10
0
1
Order By: Relevance
“…In line with prior studies, higher levels of neuroticism ( Patel et al, 2018 ) and lower levels of resilient coping style ( Shoman et al, 2021 ) associated with higher levels of emotional exhaustion, while male sex ( Purvanova and Muros, 2010 ), to be a physician or a nursing worker ( Patel et al, 2018 ; Dall’Ora et al, 2020 ), higher levels of neuroticism ( Patel et al, 2018 ), and concerns with risk of infection or death ( Bashkin et al, 2021 ) associated with higher levels of depersonalization. The present study adds to these findings by demonstrating that dissatisfaction with institutional measures to protect health care professionals physical and mental health were strongly associated with higher levels of burnout, even after accounting for these factors.…”
Section: Discussionsupporting
confidence: 83%
“…In line with prior studies, higher levels of neuroticism ( Patel et al, 2018 ) and lower levels of resilient coping style ( Shoman et al, 2021 ) associated with higher levels of emotional exhaustion, while male sex ( Purvanova and Muros, 2010 ), to be a physician or a nursing worker ( Patel et al, 2018 ; Dall’Ora et al, 2020 ), higher levels of neuroticism ( Patel et al, 2018 ), and concerns with risk of infection or death ( Bashkin et al, 2021 ) associated with higher levels of depersonalization. The present study adds to these findings by demonstrating that dissatisfaction with institutional measures to protect health care professionals physical and mental health were strongly associated with higher levels of burnout, even after accounting for these factors.…”
Section: Discussionsupporting
confidence: 83%
“…This is especially important when staff is asked to contribute in a crisis. In a study examining the organizational atmosphere during COVID‐19, Bashkin et al found that awareness of healthcare professionals’ concerns and perceptions is essential to improve the healthcare systems’ ability to confront health crises (Bashkin et al., 2021 ). Likewise, in an analysis of COVID‐19 performance, Yáñez‐Araque et al found that achievement of a good level of performance consists of the combination of leadership, commitment and a good work environment (Yanez‐Araque et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, those female nurses who do the most on‐call duty per month, or who are concerned that family members they live with may become infected, show more signs of emotional exhaustion. The association between concern over infecting family members during the COVID‐19 pandemic and emotional exhaustion has been observed in other studies (Bashkin et al, 2021), although this has been more closely associated with undergoing traumatic situations, above all in female nurses (Chen et al, 2020; Kisely et al, 2020).…”
Section: Discussionmentioning
confidence: 63%